Preparation of partially end-capped amino-terminated hyperbranched polymer and dyeing properties enhancement to polyurethane membrane. Issue 20 (October 2018) - Ren, Longfang; Geng, Jin; Wang, Na; Guo, Zidong
In this study, a series of products with different water solubility, which were named as partial end-capped amino-terminated hyperbranched polymers (HBPs) 1–6, were obtained by changing the mass ratio of raw materials. The structure was characterized by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR). The polyurethane was respectively mixed with partial end-capped amino-terminated HBPs to prepare different blend membranes by the drying method. The results showed that the water solubility of partial end-capped amino-terminated HBPs had obvious effects on the dyeing properties of blend membranes. When the mass ratio of amino-terminated HBP and single-blocked isophorone diisocyanate was 3:2, the performance of prepared partial end-capped amino-terminated HBP 4 was the best. The structures of blend membranes were characterized by FTIR spectroscopy, X-ray diffraction and scanning electron microscopy (SEM). When the mass fraction of partial end-capped amino-terminated HBP 4 was 2%, dye uptake improved from 12% to 85%. The dry-rub fastness and wet-rub fastness reached 4.5 and 3, respectively. The K/S values indicated that the surface chroma also deepened. The results indicated that partial end-capped amino-terminated HBP and polyurethane had hydrogen-bond interaction and certain phase separation.